Spritual Emotional Freedom Technique (Seft) Therapy Reduces Smoking Intensity: Experimental Study - Samsugito, Iwan; Sholichin, Sholichin; Aminuddin, Muhamad; Nur, Syukma Rhamadani Faizal; Nopriyanto, Dwi; Bahtiar, Bahtiar (Fakultas Kedokteran, 2025)
Background: Smoking behavior is an activity that can cause health problems for both smokers and people in their environment. The high prevalence of tobacco consumption has caused cigarette problems to become more serious. Increasing cigarette consumption results in a higher impact of diseases due to smoking and an increase in the death rate due to smoking, it is estimated that by 2030, the death rate of smokers in the world will reach 10 million people. Smokers in Indonesia in 2013 and 2018 remained at 24.3%, the age group of 20-24 years as the early adult group, in 2013 as much as 27.2% to 27.3% in 2018, meaning that the government's efforts to reduce the number of smokers have not been successful. To quit smoking, various ways can be done, such as counseling to change the knowledge, attitudes and actions of smokers, hypnotherapy and Spiritual Emotional Freedom Technique (SEFT). SEFT therapy combines spiritual power and psychological energy, so the therapy results are amplified because it is accompanied by prayer. The principle of work is more or less the same as acupuncture and acupressure by stimulating key points along the body's 12 energy pathways (energy meridians). Objective: To analyze the average cigarette consumption before and after SEFT therapy. Method: Quasi-experimental research experiment with one group pretest-posttest design. The number of samples was 50 respondents by measuring the average amount of cigarette consumption after 7 days of therapy. Study results: The average number of cigarettes consumed after SEFT therapy decreased from 13.16 cigarettes to 5.28 cigarettes based on the Wilcoxon test, a ρ Value of 0.00 was produced. Conclusion: SEFT therapy can reduce the intensity of smoking consumption. Suggestion: Smokers who want to quit smoking can do it with the Spiritual Emotional Freedom Technique (SEFT).